La mission insertion professionnelle des doctorants en SHS : tensions et enjeux autour des valeurs professionnelles dans les discours des enseignants-chercheurs - Stéphanie Fischer (Éducation et Socialisation)
In the reforms of the doctorate in France, the mission of helping to find an employment is recent. In comparison with other university cycles, this mission has the distinction of being devolved to academics. By extending the range of their activities, this mission interrogates the forms of professional socialization in a changing profession. This research is based on interviews with researchers about their supervisory design and their involvement in the training of doctoral candidates in the humanities and social sciences in doctoral schools. The discourse on practices and models of supervision articulate, on the one hand, the conceptions and disciplinary values of the research and, on the other hand, types of references to academic out-of-scope logics centered in particular on an "external" utility of the diploma and more integrative logics of doctoral students (research, laboratories, etc.).